2022 IEEE International Conference on Recent Advances in Systems Science and Engineering (RASSE) 2022
DOI: 10.1109/rasse54974.2022.9989657
|View full text |Cite
|
Sign up to set email alerts
|

Graph Neural Networks for HD EMG-based Movement Intention Recognition: An Initial Investigation

Abstract: Recently, high-density (HD) EMG electrodes have been proposed for improving amputees' movement/grasping intention recognition, exploiting different machine learning techniques. HD EMG electrodes are composed of a large number of closely spaced channels that simultaneously acquire EMG signals from different parts of the muscle. Given the topological properties of these devices, it is important to fully exploit the spatiotemporal information provided by the electrodes to optimize recognition accuracy. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Recently, researchers have started using GNNs to analyze sEMG signals. For instance, Massa et al [9] applied GNNs to high-density sEMG data to recognize action intentions, reaching a low classification error rate of 8.75% over 65 gestures. Vijayvargiya et al [10] used a GNN based on Pearson correlation for analyzing lower limb sEMG signals and achieved a high accuracy of up to 99.36% in recognizing different activities.…”
Section: Graph Network In Semg Signal Analysismentioning
confidence: 99%
“…Recently, researchers have started using GNNs to analyze sEMG signals. For instance, Massa et al [9] applied GNNs to high-density sEMG data to recognize action intentions, reaching a low classification error rate of 8.75% over 65 gestures. Vijayvargiya et al [10] used a GNN based on Pearson correlation for analyzing lower limb sEMG signals and achieved a high accuracy of up to 99.36% in recognizing different activities.…”
Section: Graph Network In Semg Signal Analysismentioning
confidence: 99%
“…Previous studies investigated different machine learning methods to exploit HD EMG data for gesture recognition [12]. However, to the best of our knowledge, no previous study, except our preliminary investigation reported in [13], used a graph neural network (GNN) in conjunction with HD EMG signals to identify the gesture intention of an amputee.…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing, the main contributions of our work with respect to the preliminary investigation presented in [13] are the following:…”
Section: Introductionmentioning
confidence: 99%